PERANAN DAN FUNGSI MANAJEMEN BAGI KEPALA SEKOLAH - Lubis, Rosimah (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2013)
Management covers on planning, organizing, actuating, and controlling. A headmaster as the educational organizer must pay attention on the elements of management in order his or her institution can provide a good and satisfied result. That will be effective and efficient to increase human resource and be functional and proportional to all elements of the management.